Turning Point for a New Decade of Busan Biennale : The Symposium 2009 - Sunjung Kim; Busan Biennale (Busan Biennale Organizing Committee, 2009)
Exhibition Catalog. Contributors: Akira Tatehata, Fei Dawei, Ranjit Hoskote, Yamaguchi Katsuhiro, Kambayashi, Tsunemichi, Veronique Wiesinger, Jean Hubert Martin, Henk Slager, Paul Domela, Huang Du, Elizabeth Ann Macgregor, Gerardo Mosquera, Tetsuya Ozaki, Hans D. christ, Anna Harding, Patricia Ellis, Qing Zhang, Kwok Kian Chow, Ark Fongsmut, Muhamad Supriyanto, Philippe Laleu, Noberto Santiago Roldan, Naoko Usuki.
English; Korean
Keywords: N4390-5098 Visual Arts- Exhibitions